Homeless Inuit in Montreal - Kishigami, Nobuhiro (Études/Inuit/Studies, 2008)
AbstractMigration of the Inuit into southern Canadian cities from the Arctic increased substantially during the 1980s. Approximately 10,000 out of a total of 50,000 Inuit lived outside the Canadian Arctic regions in 2006. As the number of urban Inuit is increasing, so too is that of homeless Inuit in large southern cities. It is estimated that there are more than 90 homeless Inuit in Montreal, which has an Inuit population of about 800. This paper describes the life and characteristics of homeless urban Inuit in Montreal, and the activities of the Native Friendship Centre of Montreal and of the Association of Montreal Inuit, which are essential for their survival. The Inuit of Montreal have yet to form useful social networks to ease their urban adaptation. An Inuit community centre, where information and food can be shared, should be established in Montreal to change the present situation of homeless Inuit.